PEMANFAATAN APLIKASI OWNCLOUD PADA SISTEM KEAMANAN CLOUD COMPUTING - Edy Rakhmat; Saleh Dwiyatno; Sulistiyon Sulistiyon; Agus Irawan; Ferli Setiawan (Program Studi Sistem Informasi, Universitas Banten Jaya, 2021)
Private cloud is a type of private storage or only provides limited services to an organization or an agency. OwnCloud is a company whose project is OwnCloud project. The company's slogan is